Climate Change Mitigation and Adaptation Policies: Addressing Unintended Effects on Inequalities - Gabriele M. Quinti; Federico L. Marta (Social Sciences, 2025)
It is well known that climate change exacerbates inequalities and vice versa. What is less known is that the most disadvantaged groups are also at risk of becoming non-negligible producers of emissions that cause climate change. Examples include the difficulties disadvantaged micro-entrepreneurs face in limiting the emissions of their activities, or the need for subsistence farmers to cut down trees to increase the amount of farmland. The above is mainly due to the unintended negative effects of some mitigation and adaptation (M&A) policies on the most vulnerable and their non-inclusion in the deployment of these policies. This paper aims to provide a detailed analysis in this respect, highlighting the significant limitations of some policies, which often exclude/penalise disadvantaged groups and are likely to be strongly resisted by them. The possible anti-equalisation effects of such policies, which tend to protect those who are better off more, are also highlighted. To overcome these limitations, the prospect of combining climate and social justice is emerging. However, this perspective has so far had limited impact on M&A policies, as it is only occasionally applied in practice. Conversely, specific social clauses (including social inclusion, protection of vulnerable groups, and gender mainstreaming) should be defined and applied.